Magnolol Alleviates Inflammatory Responses and Lipid Accumulation by AMP-Activated Protein Kinase-Dependent Peroxisome Proliferator-Activated Receptor α Activation - Tian, Ye; Feng, Haihua; Han, Lu; Wu, Lin; Lv, Hongming; Shen, Bingyu; Li, Zheng; Zhang, Qiaoling; Liu, Guowen (Frontiers in Immunology, 2018)
ABSTRACT Magnolol (MG) is a kind of lignin isolated from Magnolia officinalis, which serves several different biological functions, such as antifungal, anticancer, antioxidant and hepatoprotective functions. This study aimed to evaluate the protective effect of MG against oleic acid (OA)-induced hepatic steatosis and inflammatory damage in HepG2 cells and in a tyloxapol-induced hyperlipidemia mouse model. Our findings indicated that MG can effectively inhibit OA-stimulated tumor necrosis factor α (TNF-α) secretion, reactive oxygen species (ROS) generation and triglyceride (TG) accumulation. Further study manifested that MG significantly suppressed OA-activated mitogen-activated protein kinase (MAPK) and nuclear factor-kappa B (NF-κB) signaling pathways and that these inflammatory responses can be negated by pretreatment with inhibitors of extracellular regulated protein kinase (ERK) and c-Jun N-terminal kinase (JNK) (U0126 and SP600125, respectively). In addition, MG dramatically up-regulated peroxisome proliferator-activated receptor α (PPARα) translocation and reduced Sterol regulatory element-binding protein 1c (SREBP-1c) protein synthesis and excretion, both of which are dependent upon the phosphorylation of Adenosine 5’-monophosphate (AMP)-activated protein kinase (AMPK), acetyl-CoA carboxylase (ACC) and protein kinase B (AKT). However, MG suspended the activation of PPARα expression and was thus blocked by pretreatment with LY294002 and compound c (specific inhibitors of AKT and AMPK). Furthermore, MG clearly alleviated serum TG and total cholesterol (TC) release; up-regulated AKT, AMPK and PPARα expression; suppressed SREBP-1c generation; and alleviated hepatic steatosis and dyslipidemia in tyloxapol-induced hyperlipidemia mice. Taken together, these results suggest that MG exerts protective effects against steatosis, hyperlipidemia and the underlying mechanism, which may be closely associated with AKT/AMPK/PPARα activation and MAPK/NF-κB/SREBP-1c inhibition. Keywords: magnolol, Hyperlipidemia, steatosis, AMPK, PPAR alpha, inflammatory responses